Sensitization potential of medical devices detected by in vitro and in vivo methods - Svobodová, Lada; Rucki, Marian; Vlkova, Alena; Kejlova, Kristina; Jírová, Dagmar; Dvorakova, Marketa; Kolarova, Hana; Kandárová, Helena; Pôbiš, Peter; Heinonen, Tuula; Maly, Marek (ALTEX, 2021)
Medical devices must be tested before marketing in accordance with ISO EN 10993-10 in order to avoid skin sensitization. This standard predominantly refers to the in vivo test but does not exclude the use of in vitro methods that have been sufficiently technically and scientifically validated for medical device testing. It is foreseen that, due to the complexity of the sensitization endpoint, a combination of several methods will be needed to address all key events occurring in the sensitization process. The objective of this pilot study was to evaluate the sensitization potential of selected medical devices using a combination of in chemico (DPRA, OECD TG 442C) and in vitro (LuSens, OECD TG 442D) methods in comparison with the in vivo (LLNA DA, OECD TG 442A) method and to suggest a possible testing strategy for the safety assessment of medical device extracts. Overall, one of the 42 tested samples exhibited positive results in all employed test methods, while 33 samples were predicted as non-sensitizing in all three performed methods. This study demonstrated good agreement between in vitro and in vivo results regarding non-sensitizing samples; however, some discrepancies in positive classification were recorded. A testing strategy is suggested in which negative results are accepted and any positive results in the in chemico or in vitro tests are followed up with a third in vitro test and evaluated in accordance with the “2 out of 3 approach”. This strategy may reduce and replace animal use for testing the sensitization potential of medical devices.
Keywords: biotest; Animal Testing Alternatives; In Vitro Techniques; Animals; Dermatitis, Allergic Contact; alergická kontaktní dermatitida; techniky in vitro; zvířata; Pilot Projects; Skin; kůže; alternativy testů na zvířatech; pilotní projekty; Biological Assay